Promoting sustainable practices through energy engineering and asset management - Gonzalez-Prida, Vicente, 1975-; Raman, Anthony, 1968- (Engineering Science Reference, an imprint of IGI Global, 2015)
"This discusses the challenges that the developing world faces when implementing and utilizing environmentally friendly techniques for the adoption of sustainable practices in developing countries"-- Provided by publisher.
"Premier reference source"--Cover.
Keywords: Sustainable development reporting -- Developing countries.; Sustainable development -- Developing countries.; Energy development -- Developing countries.; Assets (Accounting); Developing countries.; elektronické knihy; electronic books